Robotic platform to assist in the upper extremity rehabilitation - Sidek, Shahrul Na'im (2012)
Stroke is the third largest cause of death in Malaysia. Only heart diseases and cancer kill more. It is considered to be the single most common cause of severe disability involving deficits of motor function, and every year, an estimated 40,000 people in Malaysia suffer from stroke. Any form of solutions that could help a stroke patient regain useful function of his affected limb would make them more independent in doing activities of daily living and is very much sought after. Clinical results have shown that rehabilitation procedure such as repetitive movement therapy can result in significant positive impact on majority of stroke patients. The therapy is based on goal-directed functional tasks where the set of movements known as tasks is prescribed to encourage active training of the affected limb. This therapy however is labor intensive where it requires longer time for the therapist to spend with the patient and the therapist must be trained to provide systematic, controlled, quantifiable and repetitive assistance to the complex nature of the hand movement.